The Westerly Index as complementary indicator of the North Atlantic oscillation in explaining drought variability across Europe - Vicente Serrano, Sergio M.; García Herrera, Ricardo Francisco; Barriopedro Cepero, David; Azorín Molina, César; López Moreno, Juan I.; Martín Hernández, Natalia; Tomás Burguera, Miquel; Gimeno, Luis; Nieto, Raquel (Springer, 2016)
© Springer-Verlag Berlin Heidelberg 2015. The authors wish to acknowledge Ricardo Trigo and one anonymous reviewer for their detailed and helpful comments to the original manuscript. The data for this paper are available at Spanish National Research Council repository (http://sac.csic.es/spei/database.html), at Climate Research Unit (http://www.cru.uea.ac.uk/cru/data/nao/) and the Climate Prediction centre of the NOAA (http://www.cpc.ncep.noaa.gov/data/teledoc/telecontents.shtml). This work was supported by the research project CGL2014-52135-C3-1-R and Red de variabilidad y cambio climático RECLIM (CGL2014-517221-REDT) financed by the Spanish Commission of Science and Technology and FEDER, Ephyslab (UVIGO-CSIC Associated Unit) and "LIFE12 ENV/ES/000536-Demonstration and validation of innovative methodology for regional climate change adaptation in the Mediterranean area (LIFE MEDACC)" financed by the LIFE programme. C. A-M received a postdoctoral fellowship #JCI-2011-10263. Iberdrola Renovable provided partial support from contracts. This paper analyses the influence of different atmospheric circulation indices on the multi-scalar drought variability across Europe by using the Standardized Precipitation Evapotranspiration Index (SPEI). The monthly circulation indices used in this study include the North Atlantic oscillation (NAO), the East Atlantic (EA), the Scandinavian (SCAN) and the East Atlantic-Western Russia (EA-WR) patterns, as well as the recently published Westerly Index (WI), defined as the persistence of westerly winds over the eastern north Atlantic region. The results indicate that European drought variability is better explained by the station-based NAO index and the WI than by any other combination of circulation indices. In northern and central Europe the variability of drought severity for different seasons and time-scales is strongly associated with the WI. On the contrary, the influence of the NAO on southern Europe droughts is stronger than that exerted by the WI. The correlation patterns ...